Analysis of Factors Affecting Parental Participation Towards Early Childhood Education Program - Kustiani, Anik Tri; Fauziyah, Puji Yanti (Journal of Nonformal Education, 2019)
The lack number of teachers in Wonogiri district urgea participation between parents and organizer of Early Childhood Education (ECE) program. Related to this issue, this study aimed at (1) knowing the implementation of ECE program in Wonogiri district (2) analyzing the forms of parental participation in ECE program (3) analyzing the factors affecting parental participation in ECE program implementation. This study can be catagorized as descriptive research with a quantitative approach. The data analysis technique was using descriptive statistics among ECE program in Wonogiri District, Central Java. The reserach findings showed that (1) ECE program in Wonogiri District was operated under the Education Office of Wonogiri District, especially Non-Formal and Informal Education Unit. It has ECE section focusing on developing ECE services in Wonogiri district (2) most of the respondents had a low level of participation in terms of policies, collaboration, information (3) factors affecting parental participation in ECE program implementation were education, occupation, income as well as distance between home and school.